Characteristics of intermolecular forces, physicochemical, textural and microstructural properties of preserved egg white with Ca(OH)2 addition. (1st June 2020) - Ai, Minmin; Zhou, Quan; Guo, Shanguang; Fan, Hong; Cao, Yuanyuan; Ling, Ziting; Zhou, Ledan; Jiang, Aimin
Highlights: Different ratio of Ca(OH)2 was added into pickling solution to prepare preserved egg. Preserved egg white showed more lightness as affected by 0.1% Ca(OH)2 . Addition of Ca(OH)2 delayed the alkali denaturation of egg white protein. Lose porous and regular microstructure formed as the ratio of Ca(OH)2 increased. Abstract: The effects of Ca(OH)2 on the physicochemical, mechanical and microstructural characteristics, intermolecular forces and protein patterns of preserved egg white (PEW) were investigated. Results suggested that Ca(OH)2 (0.1%) reduced the free alkalinity content and turbidity and increased the brightness of PEW. The surface hydrophobicity of PEW protein with added Ca(OH)2 decreased during the pickling period owing to the hydrophobic residues being hidden in the interior of the protein. Total content of sulfhydryl and disulfide bonds in PEW decreased. Non-specific cross-linking, hydrogen bonds and hydrophobic interactions were the primary intermolecular forces. For textural properties, hardness and springiness had obvious prominence. A loose porous and regular network-like microstructure formed as the Ca(OH)2 increased and Ca(OH)2 delayed denaturation of the PEW protein. The physical properties of PEW correlated with molecular interactions and the microenvironment. Ca(OH)2 improved the contribution of surface hydrophobicity, disulfide bonds and hydrophobic interactions to the gelation process.